Comparative proteomic and phosphoproteomic profiling of pancreatic adenocarcinoma cells treated with CB1 or CB2 agonists. Issue 9 (11th April 2013) - Brandi, Jessica; Dando, Ilaria; Palmieri, Marta; Donadelli, Massimo; Cecconi, Daniela
<x xml:space="preserve">Abstract</x> The pancreatic adenocarcinoma cell line Panc1 was treated with cannabinoid receptor ligands (arachidonylcyclopropylamide or GW405833) in order to elucidate the molecular mechanism of their anticancer effect. A proteomic approach was used to analyze the protein and phosphoprotein profiles. Western blot and functional data mining were also employed in order to validate results, classify proteins, and explore their potential relationships. We demonstrated that the two cannabinoids act through a widely common mechanism involving up‐ and down‐regulation of proteins related to energetic metabolism and cell growth regulation. Overall, the results reported might contribute to the development of a therapy based on cannabinoids for pancreatic adenocarcinoma.